A simple structured and efficient triazine-based molecule as an interfacial layer for high performance organic electronics. Issue 8 (11th May 2016) - Chakravarthi, Nallan; Gunasekar, Kumarasamy; Cho, Woosum; Long, Dang Xuan; Kim, Yun-Hi; Song, Chang Eun; Lee, Jong-Cheol; Facchetti, Antonio; Song, Myungkwan; Noh, Yong-Young; Jin, Sung-Ho
Abstract : The highly efficient organic electronic devices achieved by PO-TAZ as an interfacial layer. Abstract : Achieving the state-of-the-art performance of solution processable and flexible organic electronics requires efficient, stable, and cost-effective interfacial layers (ILs). Here, we report an alcohol soluble phosphine oxide functionalized 1, 3, 5-triazine derivative (PO-TAZ) as an IL, which remarkably tailors the work function of conductors including metals, transparent metal oxides and organic materials, making it an ideal candidate for an interfacial material in organic electronics. Consequently, PO-TAZ thin films enable the fabrication of organic and organic–inorganic (perovskite) solar cells with power conversion efficiencies of 10.04% and 16.41%, respectively, and n-channel organic field-effect transistors with an electron mobility of 8 cm 2 V −1 s −1 . Owing to the low-cost processing associated with PO-TAZ and the tremendous improvement in device performances as compared to the devices without PO-TAZ along with ambient stability, PO-TAZ is a good choice for efficient organic electronics in large area printing processes.